Analysis of factors shaping synonymous codon usage in pseudorabies virus - YIN Hua-ping; GUO Wan-zhu; XU Zhi-wen; YANG Li (浙江大学学报. 农业与生命科学版, 2007)
Synonymous codon usage and the main factors shaping codon usage in pseudorabies virus were reported in order to understand the architecture and evolution of pseudorabies virus. Firstly, Nc values, RSCU values, GC3s contents and the dinucleotide composition of pseudorabies virus genes or genome were calculated detailly to study the usage of pseudorabies virus. Secondly, correspondence analysis, a commonly used multivariate statistical approach, was carried out to analyze the factors shaping synonymous codon usage bias of pseudorabies virus genome. The results showed that: i) a strong synonymous codon usage bias on the codons ending at C or G are observed in all the pseudorabies virus genes; ii) the effect of discrimination against the use of four dinucleotides, namely CpG, CpC, CpC and GpG, is observed in codon usage of pseudorabies virus, while the dinucleotides ApA, ApT, TpA and TpT are rarely used; iii) four factors such as base composition, base mutation, translational selection and funcation of gene contribute to the synonymous codon usage in pseudorabies virus. Nc vs. GC3s plot of all pseudorabies virus genes showed that base composition completely contributed to the variation of some genes such as LLT ORF1 and LLT ORF2, and plot of GC3s- GC12s show that base mutation and translational selection are the the two facors shaping synonymous codon usage bias of pseudorabies virus. Further, plot of the two first axes generated by the correspondence analysis of RSCU values for pseudorabies virus show that the expressional level and funcation of most of the pseudorabies virus genes shape their synonymous codon usage bias. In summary, pseudorabies virus bias on G or C ending codons and compositional biases, mutational bias, translational selection, together with funcation of gene shape the synonymous codon usage of pseudorabies virus.